Identification of complications in paediatric cerebral palsy treated with intrathecal baclofen pump: A descriptive analysis of 15 years at one institution. (October 2019) - Imerci, A.; Rogers, K. J.; Pargas, C.; Sees, J. P.; Miller, F.
Abstract: Purpose: Intrathecal baclofen (ITB) treatment is used with increasing frequency in the cerebral palsy population. We describe the complications of ITB treatment, the incidence of complications, and our experience with their treatment. Methods: In a period of 15 years, 341 paediatric patients with cerebral palsy treated with ITB were evaluated. Device problems associated with the catheter or pump, or infection and complications such as cerebrospinal fluid (CSF) leak and postdural spinal headache, were reviewed. Infection was classified as early (≤ 90 days) or late (> 90 days) according to the time of onset. Results: The infection rate was 6.9% per procedure (50/720) and 14.6% per patient (50/341) over a mean 6.3 ± 3.9 years. There was a positive correlation between the risk of infection and preoperative comorbidities including epilepsy/seizure history, feeding tube, and mixed type cerebral palsy (p < 0.05, p = 0.03, p = 0.01, respectively). Eighty-five (24.9%) patients experienced 90 CSF leak episodes; 61 of these 85 patients had headache complaints as a result of CSF leak. There was a positive correlation between the risk of early infection and CSF leak (p < 0.05). Conclusions: The most common complication related to ITB was associated with pump and catheter problems. The rate of complications with the use of ITB is relatively high; however, based on the literature reports, it is the most effective treatment for severe spasticity and dystonia in patients with severe cerebral palsy. Level of Evidence: III